Characteristics of Mothers Which Affect The Low Coverage of Comprehensive Postpartum Service In The Working Area of Community Health Center of Kayen Kidul in Kediri Regency From January to August 2019 - Dintya Ivantarina; Lina Ratnawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
The utilization of postpartum maternal services in a complete manner in several regions still has not reached the target that has set by the government. Some factors that affect the coverage of comprehensive postpartum service is mother characteristics. The purpose of this research is to determine the characteristics of mothers who affect the low coverage of comprehensive postpartum service in the working area of Community Health Center of Kayen Kidul in Kediri Regency from January to August year 2019. This research was conducted in September 2019 in the working area of Kayen Kidul Community Health Center of in Kediri Regency. The design of the research used is analytical observational with a case control approach. The sampling techniques used are random sampling clusters. The samples in this study were mothers who had finished their postpartum period (more than 6 weeks to 9 months after giving birth). Independent variables are characteristic of mothers while dependent variables are coverage of the comprehensive postpartum service. Collection of data using data collection sheets with structured interview techniques and medical records in the form of maternal and child health books. Then the data is processed and analyzed univariate, bivariate and multivariate. Statistical results of bivariate statistics showed that the work (P = 0.023), pregnancy complications (P = 0.026), labor complications (P = 0.03) and the type of childbirth (P = 0.01) have an influence on the low coverage of comprehensive postpartum service. Multivariate statistical test results using binomial logistic regression obtained results in the omnibus table having P = 0.006 (P<0.05) which means the model is worth analysed. The significance value in the Hosmer and Lemeshow Test table of 0.074 (p>0.05) has the meaning of acceptable models and hypothesis testing can be performed. The value of Nagelkerke R Square 0.278 means the characteristic mother of age (P = 0.047) and the type of childbirth (P = 0.037) has an effect of 27.8% on the low coverage of the comprehensive postpartum service. The public health policy program should aim to improve the coverage of the comprehensive postpartum service by observing the characteristics of mothers in the region, namely the characteristics of maternal age and type of delivery